DONOR DARAH DI MASA PANDEMI COVID-19 - Solehudin Solehudin; Mustopa Mustopa (Ekalaya: Jurnal Pengabdian Kepada Masyarakat Indonesia, 2023)
The principle of the Indonesian Red Cross service is the spirit of neutrality and independence, having a major role in providing safe, ready-to-use blood in sufficient quantities so that it can meet the demands of patients in need. The purpose of this activity is the implementation of blood donor activities in the community as an effort to maintain health. Activities in community service include health education and blood donation. The number of residents identified as registering to become blood donors was 61 people. After being screened by the Blood Transfusion Unit officers, 49 people were eligible to donate their blood. Public understanding of the importance of blood donation has increased and blood donation activities can be carried out smoothly as expected. People who cannot donate blood should be given an education